Reflection and Executive Function: Foundations for Learning and Healthy Development - Brandon K Almy (Revista Argentina de Ciencias del Comportamiento, 2015)
Execulive function (EF) refers lo the neurocognitiveprocesses invotved in the deliberate, goal-directedmodul¿,tion of thought, aetiorl, and ernotion. Individualdifferences in EF measured in childhood predict keydeveluprTIerlt~1 outCOllllO>. dlld illtervelltiun, de~i9r1ed lofaster the healthy development of EF have lhe potential lOhelp children at risk tar a wide range of difficultÍ€s. Thisarticle briefly describes a theoretical model of EF and itsdevelopment. the Iterative ReprOCe5sing mod€l, tha1 SJ)ilnslevels of alKllysis <lOO characterizes self-regulation as theproduct of a dynarnic interaction between top-down(rdlective) and bonom-up (reactive) influences.